Caregiving and 5‐HTTLPR Genotype Predict Adolescent Physiological Stress Reactivity: Confirmatory Tests of Gene × Environment Interactions. Issue 4 (3rd March 2015) - Sumner, Jennifer A.; McLaughlin, Katie A.; Walsh, Kate; Sheridan, Margaret A.; Koenen, Karestan C.
<x xml:space="preserve">Abstract</x> A theory‐driven confirmatory approach comparing diathesis–stress and differential susceptibility models of Gene × Environment (G × E) interactions was applied to examine whether 5‐HTTLPR genotype moderated the effect of early maternal caregiving on autonomic nervous system (ANS) stress reactivity in 113 adolescents aged 13–17 years. Findings supported a differential susceptibility, rather than diathesis–stress, framework. Carriers of one or more 5‐HTTLPR short alleles (SS/SL carriers) reporting higher quality caregiving exhibited approach ANS responses to a speech task, whereas those reporting lower quality caregiving exhibited withdrawal ANS responses. Carriers of two 5‐HTTLPR long alleles (LL carriers) were unaffected by caregiving. Findings suggest that 5‐HTTLPR genotype and early caregiving in interaction are associated with ANS stress reactivity in adolescents in a "for better and for worse" fashion, and they demonstrate the promise of confirmatory methods for testing G × E interactions.